Parental first concern according to age and type in children with Autism Spectrum Disorder - Dian Dwi Sari; Irwanto Irwanto; Ahmad Suryawan; Mira Irmawati; Budi Utomo (Universitas Muhammadiyah Surabaya, 2021)
Developmental problems concerned by parents are a further diagnostic step for children with Autism Spectrum Disorder (ASD). Research is needed to find a picture of the child's behavior complained of by parents. Investigations about first concerns among parents of children with ASD and comparisons of the same with children diagnosed with other developmental disorders are rare. We want to examine the type and age of parents ‘concern in children with ASD and other developmental disorders. A cross-sectional study was conducted in Child Developmental Centre in Surabaya Indonesia from August 1 to December 30, 2019. T-test and chi-square tests were used to analyze differences in subject variables and types of concern. Most parents of both children diagnosed with ASD and non-ASD indicated first concern were in communication, social skill, and behavior problem. The average age of parents’ first concern of ASD children is 30,14 months. Significant differences were found between ASD and non-ASD groups in communications, behavior, and sensory problem concerns. There is no specific difference between parental concerns of children with ASD and non-ASD children. The average age of first concern was significantly younger for children with an ASD diagnosis than other developmental disorders.Keywords :parent concern, autism, communication.Correspondence :dian_dwisary@yahoo,com